Strategy for Building Student’s Religious Character Through School at Baiturrohman Griya Mangli Indah Jember Elementary School - Ahyah, Ummu; Ilma, Maulia Humaini (IJIE International Journal of Islamic Education, 2024)
Building Religious Character in implementing school culture at Baiturrohman Griya Mangli Indah Jember Elementary School is an important aspect in forming student’s personalities. The school integrates religious values into school culture as part of efforts to create good character in students. The formation of religious character does not only focus on religious teaching, but also on the application of moral values that reflect noble character in everyday life. This research uses a qualitative research method with a phenomenology design. Data collection techniques use observation and documentation. The data analysis technique uses Miles and Huberman analysis. Test the validity of the data by triangulation and adequacy of references. The results of this research show that the process of building religious character at SD Baiturrohman Griya Mangli Indah Jember is through Duha prayer activities, reading Juz Amma, congregational prayers, good manners, through religious activities such as Friday charity, reading Asmaul-Husnah together on Sundays. Friday, reading juz amma, memorizing daily prayers, learning Arabic and English and so on. This can raise the issue of synchronizing the school's vision and mission with what parents expect. Regarding this, teachers are supposed to be more careful in guiding students and setting a good example for them, as some kids still arrive late.